1993
DOI: 10.1099/00207713-43-1-32
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Species Concept in the Genus Dekkera by Restriction Analysis of Genes Coding for rRNA

Abstract: The gene coding for the small-subunit rRNA of 11 type strains belonging to the genus Dekkera and its anamorph, Brettanomyces, was amplified by using the polymerase chain reaction and subjected to digestion with a series of restriction endonucleases. Similarity coefficients were calculated from the number of shared and unique fragments, and a cluster analysis yielded four distinct groups with the following ascosporogenous states: Dekkera anomah, Dekkera bruxellensis, Dekkera custersiana, and Dekkera naardenensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Subsequently, Molina et al 8 ) reported a similar phenogram based on the results obtained from the restriction analyses of genes coding a small-subunit (18S) rRNA. Our experimental data described above were very similar to the phylogenetic tree reported by Clark-Walker et al 7 ) and to the phenogram reported by Molina et al, 8) especially in the 18S rRNA partial base sequencings of Dekkera and Brettanomyces species. In the 26S rRNA partial base sequencings, D. naardenensis was, however, found to be phylogenetically distant (percent similarities, 48-56; base differences 46-38).…”
Section: • 27 )mentioning
confidence: 89%
See 1 more Smart Citation
“…Subsequently, Molina et al 8 ) reported a similar phenogram based on the results obtained from the restriction analyses of genes coding a small-subunit (18S) rRNA. Our experimental data described above were very similar to the phylogenetic tree reported by Clark-Walker et al 7 ) and to the phenogram reported by Molina et al, 8) especially in the 18S rRNA partial base sequencings of Dekkera and Brettanomyces species. In the 26S rRNA partial base sequencings, D. naardenensis was, however, found to be phylogenetically distant (percent similarities, 48-56; base differences 46-38).…”
Section: • 27 )mentioning
confidence: 89%
“…2 6) The species classified presently in the teleomorphic genus Dekkera (and anamorphic genus Brettanomyces) are restricted to four: 4 ,5) The molecular-phylogenetic studies of the species in the genera Dekkera and Brettanomyces were first done by Clark-Walker et al 7 ) on the analyses of the genomic maps of their mitochondrial DNA, and followed by Molina et al 8) on the restriction analyses of their genes coding for the small subunit of rRNAs.…”
mentioning
confidence: 99%
“…Species have been defined on the basis of nuclear DNA relatedness data and the results of electrophoretic comparisons of cellular enzymes (25) and by ribotyping (15). Currently, four Brettanomyces species are distinguished: these species are Brettanomyces anomalus, Brettanomyces bruxellensis, Brettanomyces custersianus, and Brettanomyces naardenensis.…”
mentioning
confidence: 99%
“…Nuclear internal transcribed spacers (ITS) have provided an efficient means for the investigation of genetic relationship in yeasts (8,12). Lott et al (9) analyzed the nucleotide sequences of the nuclear 5.8S and ITS2 regions from multiple isolates of five Candida species.…”
mentioning
confidence: 99%